2006
DOI: 10.1111/j.1365-3156.2006.01623.x
|View full text |Cite
|
Sign up to set email alerts
|

Are maternal re‐infections with Trypanosoma cruzi associated with higher morbidity and mortality of congenital Chagas disease?

Abstract: Summary Background  Comparing two surveys performed in Bolivia in 1992–1994 and 1999–2001, we reported a significant decrease in the proportions of severe and mortal forms of congenital Chagas disease. This might be due to a reduction of vectorial density (VD) in maternal residence area, raising the question of a possible causal relationship between such VD, maternal parasitaemia and prognosis of congenital infection with Trypanosoma cruzi. Method  Comparisons of haematological and parasitological data obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 17 publications
2
33
0
4
Order By: Relevance
“…We reported mortality rates up to 13% in a Bolivian cohort of congenitally infected newborns studied between 1992 and 1994, while such rate dropped to 2% in another study in 1999-2001, when Bolivia benefited from improved socio-economic conditions, better maternal care and extended its vector control programs (limiting re-infections during pregnancy; see Section 9) . Neonatal morbidity and mortality are much higher when acute or reactivated infection (co-infection with HIV) occur during pregnancy (see Section 4; Freilij et al, 1995b;Moretti et al, 2005;Scapellato et al, 2009), as well as, likely, when chronically infected pregnant women suffer from re-infections (see Section 9; Torrico et al, 2006). Experiments in mice also show acute infection and reinfections in chronic phase inducing fetal resorptions and/or pup mortality (Mjihdi et al, 2002;Solana et al, 2002;Cencig et al, 2013; see Section 9), in relation to high blood parasite-and TNF-␣-levels (Mjihdi et al, 2002(Mjihdi et al, , 2004Solana et al, 2009).…”
Section: T Cruzi Infection and Pregnancy Outcomesmentioning
confidence: 97%
“…We reported mortality rates up to 13% in a Bolivian cohort of congenitally infected newborns studied between 1992 and 1994, while such rate dropped to 2% in another study in 1999-2001, when Bolivia benefited from improved socio-economic conditions, better maternal care and extended its vector control programs (limiting re-infections during pregnancy; see Section 9) . Neonatal morbidity and mortality are much higher when acute or reactivated infection (co-infection with HIV) occur during pregnancy (see Section 4; Freilij et al, 1995b;Moretti et al, 2005;Scapellato et al, 2009), as well as, likely, when chronically infected pregnant women suffer from re-infections (see Section 9; Torrico et al, 2006). Experiments in mice also show acute infection and reinfections in chronic phase inducing fetal resorptions and/or pup mortality (Mjihdi et al, 2002;Solana et al, 2002;Cencig et al, 2013; see Section 9), in relation to high blood parasite-and TNF-␣-levels (Mjihdi et al, 2002(Mjihdi et al, , 2004Solana et al, 2009).…”
Section: T Cruzi Infection and Pregnancy Outcomesmentioning
confidence: 97%
“…Several points about this different evolution are still poorly understood (Higuchi et al 2003). People living in endemic areas are exposed to suffer reinfections, a relevant factor even in congenital disease (Rabinovich et al 1990;Catalá et al 2004;Torrico et al 2006). We have previously demonstrated that reinfections with different T. cruzi strains have a potent role in developing early cardiac damage in the acute and indeterminate phase of experimental Chagas' disease (Bustamante et al 2002(Bustamante et al , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Data also suggest vector control programs may potentially decrease the risk of MTCT and the severity of congenital Chagas disease by decreasing maternal parasitic load [18]. Congenital transmission rates are lower in nonendemic countries compared with endemic countries [19], and congenital Chagas disease in Bolivia has been less symptomatic in recent periods [20].…”
Section: Prevention and Treatmentmentioning
confidence: 98%